2006
DOI: 10.1021/ja063636k
|View full text |Cite
|
Sign up to set email alerts
|

Tb3N@C84:  An Improbable, Egg-Shaped Endohedral Fullerene that Violates the Isolated Pentagon Rule

Abstract: The structure of isomer 2 of Tb3N@C84 has been determined through single-crystal X-ray diffraction on Tb3N@C84.NiII(OEP).2(C6H6). The carbon cage has a distinct egg shape due to the presence of a single pair of fused pentagons at one apex of the molecule. Thus, although 24 IPR structures are available to the C84 cage, Nature utilizes one of the 51 568 isomeric structures that do not conform to the IPR for this unusual molecule. The Tb3N portion of isomer 2 of Tb3N@C84 is strictly planar. One Tb atom is nestled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(202 citation statements)
references
References 23 publications
11
186
0
5
Order By: Relevance
“…The next most favored isomer is higher in energy by 13.9 kcal mol -1 than the first, which corresponds to an equilibrium fractional population of only 3% at 2000 K. This isomer and others of higher energy are unlikely to be isolated in significant yield. The isomer predicted to be most favored corresponds to experimental Gd) [32,33]. These results suggest that the encaged cluster mediates, or even controls, the formation mechanism;…”
Section: Computational Detailsmentioning
confidence: 68%
“…The next most favored isomer is higher in energy by 13.9 kcal mol -1 than the first, which corresponds to an equilibrium fractional population of only 3% at 2000 K. This isomer and others of higher energy are unlikely to be isolated in significant yield. The isomer predicted to be most favored corresponds to experimental Gd) [32,33]. These results suggest that the encaged cluster mediates, or even controls, the formation mechanism;…”
Section: Computational Detailsmentioning
confidence: 68%
“…The first reports of EMFs with carbon cages containing fused pentagon systems were those of Sc 2 @C 66 [115] and Sc 3 N@C 68 (D 3 :6140). [110] Other examples are [75b, 104,[116][117][118][119][120][121] On the other hand, spectroscopy along with DFT calculations strongly suggested that the major isomer of Dy 3 N@C 78 and Tm 3 N@C 78 both have the non-IPR carbon cage of symmetry C 2 :22 010 [122] and that Ce 2 @C 72 possesses a non-IPR carbon cage of D 2 symmetry, as in the case of La 2 @C 72 . [123] It is interesting to note that as the size of the fullerene increases, the number of fused pentagon systems decreases; for example, Sc 3 N@C 68 (D 3 :6140) has three fused pentagon systems while Gd 3 N@C 82 (C s :39 663) and M 3 N@C 84 (C s :51 365) (M = Gd, Tb, Tm) have only one ( Figure 5).…”
Section: Violations Of the Ipr With Emfsmentioning
confidence: 99%
“…The cage that encapsulates the Gd 3 N cluster (and also Tb 3 N and Tm 3 N) for the C 84 family, C s -51365, [24] does not satisfy the isolated pentagon rule (IPR). For Gd 3 N@C 88 , optical and electrochemical measurements [67] along with theoretical calculations [63,64] suggest that Gd 3 N is encaged in the IPR isomer D 2 -35 of the C 88 family, as observed for Tb 3 N. [54] Taking into account several orientational isomers, we have observed that the Gd 3 N cluster can rotate inside the C 88 cage (see Table S6 and Figure S9 in the Supporting Information).…”
Section: Da C H T U N G T R E N N U N G (Red)mentioning
confidence: 99%
“…[2][3][4] EMFs are stabilized by charge transfer from the internal metal cluster to the carbon cage, which becomes negatively charged. Apart from encapsulating single metal atoms, EMFs are also found with more than one metal atom (M 2 and M 3 ), [5][6][7][8][9][10][11][12][13][14] metal carbides (M 2 C 2 and M 3 C 2 ), [15][16][17][18][19][20][21][22][23] metal nitrides (M 3 N), [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] or even metal oxides (Sc 4 O 2 ), [41] in which M is a Group 3 or lanthanide metal atom. Interestingly, the carbon cages present in EMFs are different from those observed as empty fullerenes and in some cases they do not fulfill the isolated pentagon rule (IPR).…”
Section: Introductionmentioning
confidence: 99%